Faktor yang Mempengaruhi Kualitas Hidup Penderita Penyakit Jantung Koroner di Wilayah Kerja Puskesmas Maradekaya Kota Makassar - Nurul Annisa Sultan (YICI Publisher, 2025)
Coronary heart disease (CHD) occurs due to plaque buildup in the coronary arteries that supply oxygen to the heart muscle. The cardiovascular condition known as coronary heart disease is the leading cause of death worldwide, accounting for 35% of all deaths, or approximately 17.7 million deaths annually, according to the World Health Organization (2018). The prevalence rate of coronary heart disease is highest in Indonesia, at 1.5% of cases. According to Riskesdas, in the period 2016-2018 the number of CHD cases continued to increase, and the life expectancy and quality of life of the Indonesian population with poor health status due to CHD increased by 2.01%. In order for CHD patients to maintain optimal health, they must have a good quality of life. The purpose of this study was to identify variables that have an impact on the quality of life of coronary heart disease patients at Maradekaya Health Center. This type of research uses a cross-sectional method and is quantitative in nature. The sample size was 54, and the Slovin formula was used to determine the sample size. The method used for sampling was consecutive sampling, and data were analyzed using univariate and bivariate analysis with the chi-square test at a confidence level of 0.05. The findings showed that people with congestive heart failure (CHD) can improve their quality of life and health status by managing their condition appropriately. They also suggested that family members can improve their understanding of CHD by attending various health counseling sessions offered by health personnel and obtaining information from reliable sources.